"I" Seek Autonomy, "We" Rely on Each Other: Self-Construal and Regulatory Focus as Determinants of Autonomy- and Dependency-Oriented Help-Seeking Behavior. (June 2014) - Komissarouk, Svetlana; Nadler, Arie
There are two typical approaches to requesting help: autonomy-oriented help-seeking (asking in order to learn how to fix a problem) versus dependency-oriented help-seeking (asking a helper to fix it). This article presents three studies demonstrating a systematic impact of a person's chronic or activated self-construal (interdependent vs. independent) that operates through activated regulatory focus (prevention vs. promotion) on these two help-seeking styles. The hypothesis was tested by measuring chronic self-construal, regulatory foci, and help-seeking styles (Study 3), and by priming self-construal (Study 1) and regulatory focus (Study 2). Results show that people with an independent self-construal and a promotion focus prefer autonomy-oriented help, whereas people with an interdependent self-construal and a prevention focus seek dependency-oriented help. Mediation analysis (Study 3) shows that regulatory focus is a mediator between self-construal and help-seeking styles. The conceptual and applied implications of these findings are discussed.